Lactic Acid Bacteria from Dairy Products: Probiotic Potential and Biotherapeutic Effects - Iqbal, Muhammad Naeem; Ashraf, Asfa; Iqbal, Iqra (PSM Microbiology, 2019)
Lactic acid bacteria constitute the most important group of probiotic microorganisms, but lactobacilli species are the most commonly used probiotic microorganisms. Probiotics are living microbes which upon ingestion in appropriate number have beneficial effects on the host’s health. Increased emergence of antibiotic-resistant bacteria and the side effects of antibiotics when used for therapeutic purposes convinced to evaluate the probiotic potential of these isolates. Probiotic properties of the isolates are investigated by determination of their antibacterial activities and tolerance to bile salt and pH.